A simulation of dementia epidemiology and resource use in Australia. (27th July 2017) - Standfield, Lachlan B.; Comans, Tracy; Scuffham, Paul
Abstract: Objectives: The number of people in the developed world who have dementia is predicted to rise markedly. This study presents a validated predictive model to assist decision‐makers to determine this population's future resource requirements and target scarce health and welfare resources appropriately. Methods: A novel individual patient discrete event simulation was developed to estimate the future prevalence of dementia and related health and welfare resource use in Australia. Results: When compared to other published results, the simulation generated valid estimates of dementia prevalence and resource use. The analysis predicted 298, 000, 387, 000 and 928, 000 persons in Australia will have dementia in 2011, 2020 and 2050, respectively. Health and welfare resource use increased markedly over the simulated time‐horizon and was affected by capacity constraints. Conclusions: This simulation provides useful estimates of future demands on dementia‐related services allowing the exploration of the effects of capacity constraints. Implications for public health: The model demonstrates that under‐resourcing of residential aged care may lead to inappropriate and inefficient use of hospital resources. To avoid these capacity constraints it is predicted that the number of aged care beds for persons with dementia will need to increase more than threefold from 2011 to 2050.